Aspirin Use and Reduced Risk of Pancreatic Cancer - Risch, Harvey A. (Cancer Epidemiol Biomarkers Prev, 2016)
BACKGROUND: Few options beside avoidance of smoking and obesity are available to prevent pancreatic cancer. The association between aspirin use and risk of pancreatic cancer has been inconsistent across studies. METHODS: We performed a population-based study of 761 case and 794 control subjects frequency matched on sex and age during 2006–2011 in Shanghai, China. Participants were asked about episodes of regular use of aspirin, tablets per day or week, and ages that use started and stopped. Data were analyzed by unconditional logistic regression, with adjustments for age, sex, education, body-mass index, years of cigarette smoking, cigarettes smoked per day, Helicobacter pylori CagA seropositivity, ABO blood group, and history of diabetes mellitus. Meta-regression was carried out to summarize the literature. RESULTS: Ever-regular use of aspirin was associated with lowered risk of pancreatic cancer: odds ratio [OR] = 0.54; 95% CI, 0.40–0.73, P=10(−4.2). Risk decreased 8% per each cumulative year of use: OR(trend) = 0.92; 95% CI, 0.87–0.97; P=.0034. Across this and 18 published studies of this association, the OR for ever-regular use decreased with increasingly more recent mid-study year, for any aspirin type (P(trend)=10(−5.1)), and for low-dose aspirin (P(trend)=0.0014). CONCLUSION: Regular use of aspirin thus appears to reduce risk of pancreatic cancer by almost half. IMPACT: People who take aspirin for prevention of other diseases likely also reduce their risk of pancreatic cancer. Aside from benefits for both cardiovascular disease and certain cancers, long-term aspirin use entails some risks of bleeding complications which necessitates risk-benefit analysis for individual decisions about use.